Athenry Dominican Priory, north chancel wall, sedilia, arch and hood - O'Donovan, Danielle (My University, 2008)
Jamb of sedilia, moulding from intrados comprises: hollow, roll-and-fillet, flat surface, roll-and-fillet, chamfer. The hood, from the outer edge, comprises: roll with frontal fillet, hollow flanked by fillets, quadrant. Few hollows flanked by fillets occur in Irish architecture, in England, Morris sees them as the progenitor of the casement - another moulding that was never popular in Ireland.
Sedilia
Keywords: quadrant; Architecture, Gothic -- Ireland; Galway (Ireland)--Buildings, structures, etc.; Architecture, Dominican; Church furniture.; roll-and-fillet moldings; moldings, hollow; fillets (moldings)